Structural equation modeling of the relationships between positive thinking, self-esteem, and psychological hardiness among university students - Asiri, Ahmed Ali Al Awad; Abbady, Adel Sayed; Teleb, Ahmed Ali (International Journal of Innovative Research and Scientific Studies, 2025)
This study examined the direct and indirect relationships among positive thinking, self-esteem, and psychological hardiness in university students, grounded in positive psychology and hardiness theory. Using a quantitative, cross-sectional design, data were collected from a stratified random sample of 480 students (301 male, 179 female) at King Khalid University through three validated scales. Data analysis via SPSS and AMOS employed structural equation modeling (SEM). The proposed model demonstrated a good fit: χ²/df = 2.95 (<3), RMSEA = 0.0321 (<0.08), and incremental fit indices (NFI = 0.966, CFI = 0.968, RFI = 0.915, IFI = 0.968, TLI = 0.920) all exceeded 0.90, confirming model adequacy. Significant direct effects were found for positive thinking on psychological hardiness (0.62) and self-esteem (0.31), and for self-esteem on psychological hardiness (0.21). Positive thinking and self-esteem also showed a significant bidirectional relationship. Indirect effects emerged through the mediating role of psychological hardiness and its dimensions (sense of duty, self-control, and high self-efficacy). These findings underscore the importance of fostering positive thinking and self-esteem as interrelated psychological resources that directly and indirectly enhance psychological hardiness. Interventions targeting these constructs may enhance students’ resilience, coping capacity, and overall mental health.